Utilization of LDPE and HDPE Plastic Waste in Bitumen an Experimental Investigation - Rohit Mishra; Pankaj Agrawal (International Journal of Scientific Research in Civil Engineering, 2024)
This study presents the use of waste polythene carry bags in flexible pavement construction. Reclaimed plastic waste derived from low density polyethylene as well as from high density polythene (LDPE & HDPE) carry bags from kitchen waste and pond liner polythene have been used as additive in flexible pavements. In this study we will also add a fix percentage of Zykotherm (ZycoTherm is an odor free additive that increases moisture resistance while lowering mixing and compaction termperature up to 65° F.) Purposes of using above materials are to utilize environmentally unacceptable waste material and to develop a better material mix to resist increased traffic load, temperature effect and pressure resulted in cracks in the pavement surface. In the proposed study the plastic waste will be cleaned and cut into a size such that it passes through 2-3mm sieve using shredding machine. In this study Dense Bituminous Macadam (DBM) mix will be proposed to prepare by using plain bitumen as a control specimen and bitumen mixed with LDPE 2% and 4% & HPDE 2% ,3%,4%,5%) as by weight, with fixed percentage of Zykotherm as 1.5% by weight. The Marshall Stability test, Penetration Test,and softening point test, were conducted on control and modified DBM mixes.
Keywords: Zykoterm; LPDE; HPDE; Dense Bituminous Macadam; Marshall Stability